The transport properties of Dirac fermions in chemical vapour-deposited single-layer graphene. Issue 3 (22nd January 2017) - Arslan, Engin; Ardalı, Şükrü; Tıraş, Engin; Çakmakyapan, Semih; Özbay, Ekmel
Abstract: The electronic transport properties of Dirac fermions in chemical vapour-deposited single-layer epitaxial graphene on anSiO2 /Si substrate have been investigated using the Shubnikov–de Haas (SdH) oscillations technique. The magnetoresistance measurements were performed in the temperature range between 1.8 and 43 K and at magnetic fields up to 11 T. The 2D carrier density and the Fermi energy have been determined from the period of the SdH oscillations. In addition, the in-plane effective mass as well as the quantum lifetime of 2D carriers have been calculated from the temperature and magnetic field dependences of the SdH oscillation amplitude. The sheet carrier density (1.42 × 10 13 cm −2 at 1.8 K), obtained from the low-field Hall Effect measurements, is larger than that of 2D carrier density (8.13 × 10 12 cm −2 ). On the other hand, the magnetoresistance includes strong magnetic field dependent positive, non-oscillatory background magnetoresistance. The strong magnetic field dependence of the magnetoresistance and the differences between sheet carrier and 2D carrier density can be attributed to the 3D carriers between the graphene sheet and the SiO2 /Si substrate.